2020
DOI: 10.3390/ijms21134605
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organized Liver Microtissue on a Bio-Functional Surface: The Role of Human Adipose-Derived Stromal Cells in Hepatic Function

Abstract: The maintenance of hepatocyte function is a critical research topic in liver tissue engineering. Although an increasing number of strategies have been developed, liver tissue engineering using hepatocytes as a therapeutic alternative remains challenging owing to its poor efficacy. In this study, we developed a multicellular hepatic microtissue to enhance the function of induced hepatic precursor cells. Mouse induced hepatic precursor cells (miHeps) were self-organized in 3D with human adipose-derived s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…In a biofunctional matrix of PS coated with basic fibroblast growth factor (FGF2) and maltose binding protein, Hong et al generated functional 3D hepatocytes with hASCs as supporting cells that were cocultured with mouse induced hepatic precursor cells (miHeps) (Hong et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a biofunctional matrix of PS coated with basic fibroblast growth factor (FGF2) and maltose binding protein, Hong et al generated functional 3D hepatocytes with hASCs as supporting cells that were cocultured with mouse induced hepatic precursor cells (miHeps) (Hong et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…generated functional 3D hepatocytes with hASCs as supporting cells that were cocultured with mouse induced hepatic precursor cells (miHeps) (Hong et al, 2020).…”
Section: Rumiński Et Al Applied a Scaffold Free Low-adhesion Techniqu...mentioning
confidence: 99%
“…The development of MPCCs was inspired by earlier studies of physical homomorphic (hepatocellularhepatocellular) and heteromorphic (hepatocellular-stromal) interactions regulating hepatocyte function in vitro. [62][63][64][65] Previous researchers found that some functions could be temporarily induced when epithelial cell types from the liver were cocultured with primary human liver cells. However, in these studies, the two types of cells were randomly distributed.…”
Section: Methods Of Liver Tissue Culturementioning
confidence: 99%
“…Next, we aimed to develop a model which better resembles the overall organ structure of the liver and allows us to study liver-cancer interactions in a self-organizing matrix-free environment. We were inspired by reported microtissues from organs such as brain 45 , heart 46 and liver [47][48][49][50] that were previously used to study the tissue development and response to injury. For this, pieces of hepatocyte-like differentiated organoids were aggregated in a U-bottom plate to obtain self-organizing liver microtissues with a size of 1-2mm (Figure 6A).…”
Section: Wt Liver Acts As a Scaffold For Tumor Growth During Competitionmentioning
confidence: 99%